Justification for the Choice of a Modeling Scheme for the Hydrocarbon Preparation Process for Transportation Using Supersonic Separation - Nesterenko , Tetiana; Nesterenko, Mykola; Shevchenko, Oleksandr; Omelchenko , Oleksii (Academic journal Industrial Machine Building Civil Engineering, 2023)
A study was conducted to select a modeling scheme for the process of preparing hydrocarbons for transportation by supersonic separation. Modeling was performed in the HYSYS environment, which allowed obtaining optimal parameters for effective removal of moisture and heavy hydrocarbons. The influence of pressure and temperature changes on the efficiency of heavy hydrocarbon extraction was analyzed. The most effective modeling scheme was selected, which provides high prediction accuracy. The results obtained can be used for further optimization of gas purification technological processes and their adaptation to industrial applications.